A Jewish Gladiator at Pompeii: Reassessing the Evidence - Rocca, Samuele (Images, 2024)
This article reconsiders the iconography of a gladiator helmet found at Pompeii, which is decorated with a relief depicting a palm tree on its forehead. New evidence demonstrates that this helmet can be reasonably associated with a Jew from Judea. The first part examines the difference between the palm branch awarded to victorious athletes and gladiators as a prize and the palm tree, which in Greco-Roman art was primarily understood as a geographic indicator. Given the dating of the helmet to slightly after the end of the Great Revolt and the fact that the Iudaea Capta coinage was minted in this period in large quantities, it is quite probable that the palm tree depicted on the helmet was a reference to Judea. The second part focuses on the griffin that decorates the crest. While images depicting animals were at odds with the tendency to aniconism, which became almost dominant in late Second Temple period Judea, a passage of the Tosefta and the relief of the Triumphal Arch of Titus, which depicts similar creatures, raise the possibility that this mythological creature could be associated with a Jew from Judea after all. The third part demonstrates that the owner of this helmet was a gladiator known as a thraex, who was typically armed with the sica. This weapon, in turn, could associate the owner of the helmet with the sicarii, a rebel group active in Judea in the last years of Roman rule and during the Great Revolt. The fact that the term sicarius is associated in Roman law with crimes often related to banditry could suggest that the owner of the helmet was sentenced to become a gladiator because of his activities as a Jewish rebel.